Pemanfaatan Bahan Sederhana pada Praktikum Mandiri: Kajian Motivasi dan Persepsi Mahasiswa - Annisa Meristin; Sunyono Sunyono; Siti Marfu’ah (Chemistry Education Department of Education and Teaching Faculty, 2022)
Practical activities during the covid pandemic are difficult to do because all learning has turned to online learning. So that students are required to carry out independent practicum at home, even though laboratory equipment and materials are quite expensive and difficult to obtain. A breakthrough is needed so that the practicum can still be carried out. One of them is independent practicum using simple equipment and materials. Independent practicum is implemented in basic chemistry courses during the odd semester. However, reflection on the practicum is needed to identify motivation and an opinion from student. The research design used was descriptive qualitative research. The research was conducted on students of the Chemical Education Study Program, University of Lampung. Data was collected by using a questionnaire through a Mentimeter. The results showed that (1) students were highly motivated to participate in independent practicum because it was interesting, (2) students' perception of independent practicum is very good, this is shown by the number of students who are helped in understanding the concept of chemistry after doing independent practicum, (3) the obstacle experienced by students during independent practicum is the difficulty of signaling in some areas which causes the upload of independent practicum videos to be often late. This research is relevant and can be a practical breakthrough for both lecturers and teachers who have limited laboratory equipment and materials by loosening the collecting of practicum videos.